Competency level of employability skills among the apprentices of the National Dual Training System: a comparative analysis of industry perception by company status - Saari, Hazril Azmin; Mat Rashid, Abdullah (Contemporary Research Center, 2013)
This study seeks to examine the competency level of employability skills among the apprentices of the National Dual Training System (NDTS) according to the perception of the employers in the industry. The study sample comprises of 56 industrial employers who had given apprentices practical/hands-on training in 2012. Respondents are the industrial bosses in various sectors and different types of companies which are directly involved in training the NDTS apprentices in that particular year. 63 percents of the respondents are from small and medium-sized industries SME), 23 percents are multi-national companies (MNC) and 14 percents are government-linked companies (GLC). The data is obtained via survey and interviews. The result shows that overall competency level of employability skills of the apprentices’ is shown to be at a moderate level. The sub-constructs for the mean of basic skills are 3.23, the mean for personal skills 3.66 and the mean for working as a team 3.35 of 5 point scales. The study findings for the differences of the type of company suggest that the mean score for the employability skill competency among the apprentices in the MNC companies is significantly higher (M= 4.0, SD= 0.125) than the GLC companies (M=3.50, SD=0.227) and the SME companies (M= 3.14, SD= 0.361).The one-way ANOVA test demonstrates a significant difference according to the types of companies which train the apprentices in 2012, F(2,53) = 45.6, p<0.05.As there is a significant difference following the type of companies, the test of Post Hoc Scheffe is conducted to evaluate the source of differences in further detail.